Nonwoven/Nanomembrane Composite Functional Sweat Pads - Muhammad Bilal Qadir; Mohammed Jalalah; Muhammad Usman Shoukat; Adnan Ahmad; Zubair Khaliq; Ahsan Nazir; Muhammad Naveed Anjum; Abdul Rahman; Muhammad Qamar Khan; Rizwan Tahir; M. Faisal; Mabkhoot Alsaiari; et al. (Membranes, 2022)
Sweat is a natural body excretion produced by skin glands, and the body cools itself by releasing salty sweat. Wetness in the underarms and feet for long durations causes itchiness and an unpleasant smell. Skin-friendly reusable sweat pads could be used to absorb sweat. Transportation of moisture and functionality is the current challenge that many researchers are working on. This study aims to develop a functional and breathable sweat pad with antimicrobial and quick drying performance. Three layered functional sweat pads (FSP) are prepared in which the inner layer is made of an optimized needle-punched coolmax/polypropylene nonwoven blend. This layer is then dipped in antimicrobial ZnO solution (2, 4, and 6 wt.%), and super absorbent polymer (SAP) is embedded, and this is called a functional nonwoven (FNW1) sheet. Electrospun nanofiber-based nanomembranes of polyamide-6 are optimized for bead-free fibers. They are used as a middle layer to enhance the pad’s functionality, and the third layer is again made of needle-punched optimized coolmax/polypropylene nonwoven sheets. A simple nonwoven-based sweat pad (SSP) is also prepared for comparison purposes. Nonwoven sheets are optimized based on better comfort properties, including air/water vapor permeability and moisture management (MMT). Nonwoven webs having a higher proportion of coolmax show better air permeability and moisture transfer from the inner to the outer layer. Antimicrobial activity of the functional nonwoven layer showed 8 mm of bacterial growth, but SSP and FSP showed only 6 mm of growth against Staphylococcus aureus. FSP showed superior comfort and antibacterial properties. This study could be a footstone toward highly functional sweat pads with remarkable comfort properties.